If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.43x + 33 = 0 Reorder the terms: 33 + 0.43x = 0 Solving 33 + 0.43x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33' to each side of the equation. 33 + -33 + 0.43x = 0 + -33 Combine like terms: 33 + -33 = 0 0 + 0.43x = 0 + -33 0.43x = 0 + -33 Combine like terms: 0 + -33 = -33 0.43x = -33 Divide each side by '0.43'. x = -76.74418605 Simplifying x = -76.74418605
| 3(2x+6)=5x+16 | | 6a+19=34+a | | 4x*x-12x-35=0 | | 4(x+2)+48=-4x | | 10x+5=11x-5 | | 5(-3)(4-7)+9=49 | | 2x+11=-9x-8x | | 9x+2=5x+18 | | h+b+h+b= | | 9(x+5)+3(x+5)=5x-5 | | 6+4x-2=9x+4-4r | | -25+5x=50 | | 3/10-3/56 | | 3(-4)=-12 | | 1/6(4x+70)=3x | | 2x+36=48 | | 10(t-5)+4t=7(t+5)-9 | | 2y+84=106 | | 6+(-7/4) | | 5(x-6y)= | | -7x+x-7-4x+3=6(X-2)x+19 | | 3.25n=-39 | | 3.25=-39 | | (25/36)=x | | 3=-1-j | | -26+n=39 | | 1/4*-7 | | p+1=-1 | | n/3.25=4 | | (4-2y)/2 | | 2(x+5)=4x-1 | | 1=-2-j |